Analysis of the beginning of the early flight phase of the ski jump in athletes with different performance levels - Janura, M.; Cabell, L.; Svoboda, Z.; Elfmark, M.; Janurova, E. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
BACKGROUND: Obtaining a long jumping distance is necessary in order to succeed among the best competitors in the Nordic combined. The body movement during the take-off and early flight is considered to be the most important factor for length of the jump. OBJECTIVE: The purpose of this study was to assess the technique of the start of the early flight phase among three groups of Nordic combined competitors representing different performance levels, and to compare them with a group of ski jumpers. METHODS: Thirty competitors from both sport disciplines (Nordic combined and ski jumping), who performed ski jumps using an HS-134 m jumping hill during the 2009 Nordic World Ski Championships in Liberec, were divided into three subgroups based on jump length. Two-dimensional kinematic data were collected for the lower extremities, the trunk, and the skis of the competitors. RESULTS: The elite Nordic combined group showed a greater in-run velocity than did the two other performance groups (p CONCLUSIONS: The results indicated that ski jumping competitors took a better aerodynamic position in the section 0-5 m behind the edge of the jumping hill. The Nordic combined competitors used a higher average in-run velocity to achieve ski jump length comparable to those of ski jumpers.